Yellowstone Dutton Ranch w Mrągowie. W oczekiwaniu na kolejny sezon .......... 351 (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
YELLOWSTONE DUTTON RANCH IN MRĄGOWO. WAITING FOR THE NEXT SEASONThis essay is a reflection on the heritage of the Mrągowo Country Picnic in relation to the currently popular TV series Yellowstone. From a historical perspective, the text explores how the festival’s heritage narrative evolves in response to changing cultural and geopolitical contexts.